Progression Patterns and Post-Progression Survival in Recurred Intrahepatic Cholangiocarcinoma Patients: A Novel Prognostic Nomogram Based on Multicenter Cohorts - Zhao, Chongyu; He, Chaobin; Lu, Jiawei; Huang, Xin; Chen, Cheng; Lin, Xiaojun (Frontiers in Oncology, 2022)
The post-progression survival (PPS) of recurred iCCA patients relates to the characteristics of tumor progression. And the prediction model of PPS in those patients has not been well established. This study aimed to develop a novel nomogram for predicting PPS in recurred iCCA patients. Clinical characteristics were retrospectively collected in 396 patients diagnosed with iCCA from cohorts of Sun Yat-sen University Cancer Center (SYSUCC) and the First Hospital of Dalian Medical University (FHDMU). The PPS in patients with different progression patterns was investigated. The nomogram of PPS was established with the Cox regression model in the primary cohort. Then the nomogram was verified in the external validation cohort. Liver progression was the commonest pattern (42.08%) in recurred iCCA patients, while patients with local LN progression had significantly better PPS than those with other patterns. The independent prognostic factors comprised elevated CEA levels, tumor differentiation, N stage 8th, adjuvant therapy, Local LN metastasis, Liver Metastasis only, and Multiple Metastasis. The nomogram constructed on these factors achieved satisfied C-index of 0.794 (95%CI 0.769-0.828) and 0.827 (0.779-0.876) for the training and validation cohorts, respectively. These values were significantly higher than those of the 8th TNM stage system (all P<0.001). The recurred iCCA patients could be precisely classified into high- and low-risk groups according to the cutoff point of this nomogram (P<0.01). The investigation of progression patterns and the development of this nomogram can offer new evidence to precisely post-operative and post-progression management of iCCA patients.